Imaging secondary ion mass spectrometry of a paint cross section taken from an early Netherlandish painting by Rogier van der Weyden - Keune, Katrien; Boon, Jaap J (Analytical chemistry (Washington), 2004)
Static secondary ion mass spectrometry (SIMS) is introduced as an analytical technique for the examination of paint cross sections to obtain simultaneous information about the nature and distribution of pigments and the binding medium from a single sample. A sample taken from the virgin's blue robe in the panel painting The Descent from the Cross (Museo del Prado, Madrid) of the Early Netherlandish painter Rogier van der Weyden (1399/1400-1464) was selected for investigation. Data were compared with reference compounds and reference lead white linseed oil paint and egg tempera paint. The static SIMS technique gave position-sensitive mass spectra that were used to image the elemental distribution of pigments and the molecular signature of components of the oleaginous binding medium. SIMS ion images of sodium and aluminum superimposed with the blue pigment ultramarine and those of copper, lead, and calcium with the position of the mineral pigments of azurite, lead white, and chalk, respectively. Preserved monocarboxylic acids of palmitic and stearic acids present as fatty acids and fatty acid lead soaps pointed to the use of linseed oil as a binding medium. Images from the oleaginous binding medium fatty acids show a correlation with the three main paint layers. The observed palmitic/stearic acid ratios for the two ultramarine layers and azurite layers are 1.3, 1.4, and 1.8, respectively. Fatty acids and fatty acid soaps show highest ion yields near lead white, a mineral pigment that serves as a natural chemical drier and is proposed to act as a template for the initial grafting of the polyunsaturated triglycerides of the linseed oil. Almost no fatty acids were detected in other layers visible by light microscopy. The fatty acid lead soaps point toward a mature ionomeric oil paint system that developed over centuries. SIMS evidence for egg tempera, still used in the 15th century, is not detected in the paint cross section. SIMS images correlate well with SEM/EDX, FT-IR and light microscopic images and the SIMS spectral data additionally support the identification of pigment particles, lead soaps, and other binding medium components.